An STM – SEM setup for characterizing photon and electron induced effects in single photovoltaic nanowires. (November 2018) - Holmér, Jonatan; Zeng, Lunjie; Kanne, Thomas; Krogstrup, Peter; Nygård, Jesper; de Knoop, Ludvig; Olsson, Eva
Abstract: Vertical arrays of semiconductor nanowires show great potential for material-efficient and high-performance solar cells. The characterization and correlation between material structure and properties of the individual nanowires are crucial for the continued performance improvement of such devices. In this work, we developed a method with a scanning tunneling microscope (STM) probe inside a scanning electron microscope (SEM) to enable the studies of single photovoltaic nanowires. The STM probe is used to contact individual nanowires in ensembles. We combine the STM-SEM with an in situ light emitting diode (LED) illumination source to study both the electrical and photovoltaic properties of vertical GaAs nanowires with radial p-i-n junctions. We also illustrate that the local charge separation ability within the nanowires can be studied by electron beam induced current (EBIC) measurements. The in situ SEM setup allows the correlation between properties and nanowire structure. The data show that the quality of the electrical contact to the semiconductor nanowire is crucial to be able to investigate the inherent properties of the nanowires. We have established a procedure to make high-quality ohmic contacts to the nanowires with the STM probe. We also show that the effect of mechanical strain on the electrical properties can be investigated by the STM-SEM setup. Graphical abstract: fx1 Highlights: An STM – SEM characterization technique is applied to single nanowire solar cells. Photovoltaic quality of as-grown radial p-i-n junction GaAs nanowires is studied. Ohmic contact between STM probe and nanowire is reproducibly realized.